THE IMPORTANCE OF PRODUCTION AND IMPORT FOR ENSURING FOOD AVAILABILITY IN ROMANIA - Agatha POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the importance of production and import in food availabilities in Romania in the period 2015- 2020,using the data provided by National Institute of Statistics. the following indicators were studied: total consumption, consumption per inhabitant, production, production/consumption rate, import, import/consumption rate, export, trade balance, import/export ratio, food availabilities, production share and import share in food availabilities, self-sufficiency rate. Dynamic analysis, mean, growth rate in 2020 versus 2015, comparisons were the main tools used for data processing. The results showed that consumption increased for fruits, vegetables, meat, fish, and declined for potatoes, cereals, sugar and eggs, as consumers are more oriented to a healthier diet. Production increased for fruits (26.7% ), meat( 3.3%), potatoes (2.8%), but it declined for sugar (-65%), eggs (- 17%), milk (-5%), fish (-5%), and vegetables (-2.7%). In 2020 vs.2015, production covered consumption of cereals, potatoes, fruits, eggs and milk, but not for meat and fish. Imports increased for all the products, the growth rates varying between 136.7% for sugar and 17% for fish and cereals. The coverage rate of consumption by import was 101% for cereals, 97% for sugar, 91% for fish, 64% for fruits, 39% for meat, 38% for fats, 29% for potatoes, 23% for milk, 17% for vegetables and 10% for eggs. Agro-food export increased for all the products, but with a lower rate than import, resulting a negative trade balance, cereals and honey being excepted. Import/export ratio was the smallest for cereals (0.34), but high for the other products (21.5 for potatoes, 13.7 for fish, 12 for fruits, 10.1 for vegetables, 4 for milk, 3.8 for sugar, and 3.6 for meat). Self-sufficiency rate was over 100% for cereals and honey, and below 100% for all the other products, the lowest level being for fish and sugar. The share of import in food availabilities was 91% for fish, 89% for sugar, 39% for meat, 35.9% for fruits, 32.4% for cereals, 30% for fats, 20.7% for vegetables, 18.4% for milk, 17.6% for potatoes, and 8.1 % for eggs. As a conclusion, the high share of imports is a result of the incapacity of agricultural production to cover market needs for all the product categories. Farmers have to increase productivity, product quality, to join in associative forms, and create short supply food chains to sell their products. Imports are justified mainly in cases where production is not sufficient to cover the internal market.